Analysis Of The Use Of Moringa Leaf (Moringa oleifera) Liquid Organic Fertiliser (LOF) On The Growth And Yield Of Pak Choi (Brassica rapa l.) - Budi Hery Kiswanto; Umi Kulsum Nur Qomariah; Siti Aminatuz Zuhria (AGARICUS: Advances Agriculture Science & Farming, 2026)
The purpose of the research to determine the effect of providing liquid organic fertilizer (POC) from moringa leaves on several parameters of pakcoy plants, namely plant height, number of leaves, root volume, wet weight of plants, and growth rate. The study was conducted in April - June 2025 in a yard located in Sentulan Hamlet, Bongkot Village, Peterongan, Jombang. The method used in this study is a quantitative method with a Completely Randomized Design (CRD). This method applies 5 treatments, namely P0 (Control Land), P1 (Provision of 30 ml/L moringa leaf POC), P2 (Provision of 40 ml/L moringa leaf POC), P3 (Provision of 50 ml/L moringa leaf POC), and P4 (Provision of 60 ml/L moringa leaf POC). The results of the study showed that from the results of the ANOVA, plant height was known to be Fhit (0.64) < F5% (2.57), the number of leaves was known to be Fhit (0.93) < F5% (2.57), wet weight was known to be Fhit (0.55) < F5% (2.57), and growth rate is known Fhit (0.69) <F5% (2.57) meaning that liquid organic fertilizer of Moringa leaves had no effect on the four growths, but on root volume it was known that Fhit (2.94) > F5% (2.57), meaning that liquid organic fertilizer of Moringa leaves only had an effect on the growth of the root part. So that the liquid organic fertilizer (POC) treatment of moringa leaves only affects the root volume of the pakcoy plant.